Specificity of endothelial cells in endothelial dysfunction of diabetic kidney disease and their crosstalk with neighboring cells: an updated review - Li, Jiarui; Zhang, Yue; Sun, Xiao; Guan, Huifang; Wang, Jingshuo; Zhao, Shuang; Tian, Chuanxi; Han, Mingda; Ma, Kaile; Li, Min (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD), a major microvascular complication of diabetes, is characterized by persistent proteinuria, a declining glomerular filtration rate (GFR), and distinctive pathological alterations, often progressing to end-stage renal disease (ESRD). Renal endothelial cells homeostasis is essential for maintaining glomerular architecture and function, sustaining an anti-inflammatory and antithrombotic environment, and preventing fibrosis. Although injury to intrinsic renal cells has been widely studied, the distinct contribution of glomerular endothelial cells (GECs) to endothelial dysfunction and their crosstalk with neighboring cells remain poorly defined. Crosstalk between renal cells is critical for integrity of the glomerular filtration barrier (GFB) and overall renal homeostasis. This review provides an updated and systematic overview of the distinct roles of GECs in DKD, encompassing their phenotypic heterogeneity, early glycocalyx damage with increased vascular permeability, and late-stage renal fibrosis. It further elaborates on the dynamic interactions between GECs and podocytes, mesangial cells (MCs), and tubular epithelial cells (TECs). Additionally, we summarize therapeutic strategies targeting endothelial function in DKD, including direct anti-hyperglycemic interventions, non-glycemic interventions, and approaches focused on endothelial injury biomarkers. In summary, this review highlights the distinct and underappreciated role of endothelial cells in DKD, emphasizing their therapeutic potential as a primary target.